MEMBONGKAR POSISI MEDIA SOSIAL INSTAGRAM SEBAGAI PELANGGENG KAPITALISME DI ERA NEOLIBERAL (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
The growth of e-commerce and social commerce every year both the number and level of customer trust continues to increase. The phenomenon of celebgrams and influencers on Instagram as an s-commerce platform shows how the industrial revolution 4.0 is able to have a significant impact on the economy, because MSMEs are now able to market their products easily and utilize influencer services for branding. But on the other hand, content in the era of digital society actually refers to the typical Debord-style spectacle society. Influencers actually display a consumptive lifestyle through their content so that it becomes an